Analisis Semiotik Makna Judul dan Representasi Konflik dalam Film Dokumenter Pesta Babi - Hermawan Yulianto; Hasan Mukti Iskandar (Institut Nalanda, 2026)
This article discusses how the title and conflict narration in the documentary film Pesta Babi: Kolonialisme di Zaman Kita (2026) produce layered meanings. The study applies a qualitative interpretive design with Roland Barthes semiotics as the main analytical lens, particularly the concepts of denotation, connotation, and myth. The data were obtained from the film text, the title as an independent sign, public statements related to the film, and secondary materials concerning Papuan agrarian issues. The analysis indicates that the phrase Pesta Babi does not merely refer to a traditional ceremony, but also functions as an ironic sign that exposes unequal relations between indigenous communities, state development discourse, and extractive interests. The film presents agrarian conflict, ecocide, and militarization as connected parts of contemporary colonial practice. By foregrounding indigenous voices and symbolic resistance, the documentary challenges the dominant myth that development is always neutral and universally beneficial. This study contributes to media and communication studies by showing how documentary titles and cinematic strategies can become sites of ideological struggle.